(untitled) (LACCEI, 2024)
The objective of the research was to design the standardization of business processes for productivity in an SME of the commercial sector engaged in the provision of industrial supplies. The study was non-experimental, prospective design, applied classification, cross-sectional, observational and with a qualitative approach. Likewise, observation, interview and documentary review techniques were used, and instruments such as observation form, interview guide and registration form, which were applied to a sample of 5 commercial processes. Concluding that the redesign of the standardization of the processes for the commercial area in the TO BE model were those of Commercial Management, Customer Follow-up, Quotation of products and services, Quotation of hydrocarbons and After-sales Service, where the proposed model is aligned to the needs of the business line In turn, the proposed model proposes to eliminate repetitive activities, better define the roles of the intervening actors, reduce delay times and therefore favor the productivity of the studied SME, making use of flow charts considering three averages to measure the current productivity level of the AS IS model, getting a total average yield of 99.00% of efficiency, 61.72% of efficacy and 81.26% of effectiveness